Exploring the Immunopathogenesis of Pregnancy With COVID-19 at the Vaccination Era - Lv, Dan; Peng, Jing; Long, Rui; Lin, Xingguang; Wang, Renjie; Wu, Di; He, Mengzhou; Liao, Shujie; Zhao, Yun; Deng, Dongrui (Frontiers in Immunology, 2021)
Since December 2019, Wuhan, China, has experienced an outbreak of coronavirus disease (COVID-19), which is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Pregnant women are deductively considered to be in immunosuppressive condition for the safety of semi-allograft fetuses, which increases the risk of being infected by the virus. In this review, we analyzed the unique immunological characteristics of pregnant women and reviewed their known outcomes at different trimesters from the perspective of underlying mechanisms that have been studied and speculated so far.